2004
DOI: 10.1159/000080762
|View full text |Cite
|
Sign up to set email alerts
|

Serum Insulin-Like Growth Factor I Levels in Growth Hormone-Deficient Adults: Influence of Sex Steroids

Abstract: Measurement of serum insulin-like growth factor I (IGF-I) concentrations remains the single most important tool in the evaluation of growth hormone (GH) replacement in GH-deficient adults, and the therapeutic goal is to maintain the level within the age-adjusted normal range. In healthy adults, IGF-I levels do not differ between males and females, whereas spontaneous GH secretion is approximately twofold higher in females. Untreated GH-deficient women exhibit lower IGF-I levels compared with men, and the incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Our study population consisted of 10 individuals, four of whom were females. We may not have appreciated this IGF-1 mediated effect due to our smaller sample size, or due to the inclusion of females in our study population, as estrogen suppresses hepatic production of IGF-1 [35]. Further studies are indicated to better define both the IGF-1 modulation of CD34+, VEGFR2(KDR)+, and AC133+ cells in diverse populations and also the possible impact of the somatotropic axis on the late-outgrowth EPC population.…”
Section: Discussionmentioning
confidence: 96%
“…Our study population consisted of 10 individuals, four of whom were females. We may not have appreciated this IGF-1 mediated effect due to our smaller sample size, or due to the inclusion of females in our study population, as estrogen suppresses hepatic production of IGF-1 [35]. Further studies are indicated to better define both the IGF-1 modulation of CD34+, VEGFR2(KDR)+, and AC133+ cells in diverse populations and also the possible impact of the somatotropic axis on the late-outgrowth EPC population.…”
Section: Discussionmentioning
confidence: 96%
“…Whole milk and other high-fat dairy products have a higher estrogen concentration than their low-fat counterparts (Wolford and Argoudelsi, 1979). Since estrogens decrease circulating IGF-I levels (Jorgensen et al, 2004;Veldhuis et al, 2005), it is possible that their presence in high-fat dairy foods could explain the observed association. Alternatively, increased insulin sensitivity among high-fat dairy consumers may have improved ovulatory function.…”
Section: Discussionmentioning
confidence: 99%
“…Recognized factors influencing IGF1 status in GHD patients include age (20), gender (13,(21)(22)(23)(24)(25)(26), exogenous estrogen therapy (27), and prolactin status (28).…”
Section: Diagnosis Of Ghdmentioning
confidence: 99%